Solitons, breathers and rogue waves for the coupled Fokas–Lenells system via Darboux transformation. (February 2017) - Zhang, Y.; Yang, J.W.; Chow, K.W.; Wu, C.F.
Abstract: In this paper, a vector generalization of the Fokas–Lenells system, which describes for nonlinear pulse propagation in optical fibers by retaining terms up to the next leading asymptotic order, is investigated. Higher-order soliton, breather, and rogue wave solutions of the coupled Fokas–Lenells system are derived via the n -fold Darboux transformation. Meanwhile the dynamic characteristics of those solitary wave solutions have been discussed.